2021
DOI: 10.3390/medicina57070704
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Functionality Following Hemodialysis Initiation in End-Stage Kidney Disease—A Single-Center, Prospective, Cohort Study

Abstract: Background and Objectives: Two-dimensional speckle tracking echocardiography (2D-STE) is viewed as an outstanding technique, competent of uncovering earlier subclinical myocardial anomalies compared to conventional echocardiography. A few endeavors adopted 2D-STE as a tool to estimate right ventricular (RV) function in subjects with end-stage kidney disease (ESKD). There is no published prospective study on an adult ESKD cohort exploring the consequences of commencing elective hemodialysis (HD) on RV behavior.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Notably, the systolic function of the right ventricle demonstrates a significant decline during the progression of CKD, likely influenced by volume status. It has been observed that RV ejection fraction improves during the initial phase of hemodialysis [27][28][29]. TRPG serves as an indicator of afterload on the right ventricle, and reducing TRPG levels has been associated with improved cardiovascular prognosis [30].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the systolic function of the right ventricle demonstrates a significant decline during the progression of CKD, likely influenced by volume status. It has been observed that RV ejection fraction improves during the initial phase of hemodialysis [27][28][29]. TRPG serves as an indicator of afterload on the right ventricle, and reducing TRPG levels has been associated with improved cardiovascular prognosis [30].…”
Section: Discussionmentioning
confidence: 99%
“…Tasana in 2021 suggested that a low value of RV strain carries the burden of mortality in hemodialysis patients, independent of any other aggravating or ameliorating factor [10].…”
Section: Discussionmentioning
confidence: 99%
“…There are studies assessing short term changes of RV parameters e.g. TAPSE, S', FAC, MPI, before and after a single HD procedure, that show improvement of RV function associated with preload reduction [13].…”
Section: Discussionmentioning
confidence: 99%